Imagining research together and working across divides: Arts-informed research about young people's (post) digital lives. (February 2023) - Collier, Diane R; Perry, Mia
Research that 'grows apart' from its original design and proposal is not uncommon, especially when involving participatory and creative methods. However, the disconnect between research intentions and research realization is seldom probed for the insights offered; this paper addresses this gap. Taking up the conceptual lens of research imaginaries, this paper dives into the tensions and discoveries experienced in between the design and the practice of a multi-site participatory research project. The study involved two groups of young people, in two cities in two countries, with a focus on digital lives. In a commitment to collaboration with artists, senior researchers, research assistants, and young people in community spaces, a complex project emerged. This paper describes the tensions and possibilities of an emergent methodology and in doing so argues for increased attention to the movement of research designs; rather than the adherence to them.